2023
DOI: 10.1097/md.0000000000032398
|View full text |Cite
|
Sign up to set email alerts
|

A review of venous thromboembolism risk assessment models for different patient populations: What we know and don’t!

Abstract: Venous thromboembolism (VTE) is a common cause of morbidity and mortality in hospitalized patients. Globally, it is also the third leading vascular disease, after myocardial infarction and stroke. The incidence of VTE is reportedly higher in Western countries than in Asian countries. However, recent reports suggest an increasing incidence of VTE in Asian countries, including India. Since VTE is largely a preventable disease, early identification of risk factors can lead to disease prevention or the adoption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Caprini RAM outperformed Padua RAM in terms of sensitivity, PPV, and NPV, in consistency with the results of earlier investigations, which reported that the Caprini RAM was more accurate than the Padua RAM at making predictions. 20 , 26 , 27 In the present study, risk factors such as older age (age >70 years), previous VTE, reduced mobility, acute infection, and low or high Caprini score classification were significantly higher in VTE patients than in non-VTE patients. This result is in accordance with the findings of Kupelian et al 28 and Alabdulkarim et al 29 Therefore, it appears that the additional evaluation parameters in the Caprini RAM could account for its greater accuracy compared with the Padua model, and the low sensitivity of the Padua RAM for VTE could be related to the fact that many patients with multiple high risks were undervalued in that model.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Caprini RAM outperformed Padua RAM in terms of sensitivity, PPV, and NPV, in consistency with the results of earlier investigations, which reported that the Caprini RAM was more accurate than the Padua RAM at making predictions. 20 , 26 , 27 In the present study, risk factors such as older age (age >70 years), previous VTE, reduced mobility, acute infection, and low or high Caprini score classification were significantly higher in VTE patients than in non-VTE patients. This result is in accordance with the findings of Kupelian et al 28 and Alabdulkarim et al 29 Therefore, it appears that the additional evaluation parameters in the Caprini RAM could account for its greater accuracy compared with the Padua model, and the low sensitivity of the Padua RAM for VTE could be related to the fact that many patients with multiple high risks were undervalued in that model.…”
Section: Discussionmentioning
confidence: 42%
“…Whereas the Caprini model is more widely used in surgical patients, the Padua model caters specifically to medical patients. 20 Both models have their strengths and limitations, and their selection should be based on patient population and clinical context. Despite a large proportion of hospitalized patients appearing to be at high risk for the consequences of VTE, thromboprophylaxis is still not adequately carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 This makes the method an effective tool in supporting DVT diagnosis. 36 This scoring method is considered a helpful instrument in diagnosing DVT, allowing for more precise subsequent steps, including administering anticoagulant therapy, by referring to established diagnostic algorithms. 37 In this study, it was found that all 21 respondents (100%) had asymptomatic DVT.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of previous local studies of VTE in the study population, the prevalence of VTE in other studies of hospitalized populations is around 10-60% [19][20][21] .A pre-experiment was conducted by selecting a large number of quali ed individuals, with a margin of error of 10% and a signi cance level of 0.05, to estimate the VTE incidence rate of 25%. The required sample size was 1191 to ensure the accuracy of medical terminology.…”
Section: Sample Sizementioning
confidence: 99%